Sekolah sebagai Sistem Sosial: Analisis Perannya dalam Menguatkan Nilai-Nilai Multikultural Siswa di SMAN 4 Mataram - Almira Wulandari; Edy Kurniawansyah; Lianda Dewi Sartika (Mataram University, 2026)
Schools, as social systems, play a crucial role in fostering a multicultural educational environment amidst diversity. This is evident at SMAN 4 Mataram, which exhibits a high degree of social, cultural, and religious diversity, thereby necessitating the reinforcement of tolerance, cooperation, and respect for differences to prevent social conflict within the school environment. This study aims to analyze the role of the school as a social system in reinforcing multicultural values among students at SMAN 4 Mataram. This study employs a descriptive qualitative approach, utilizing data collection techniques such as observation, interviews, and documentation. The results indicate that the school, as a social system, fosters a multicultural educational environment through its structural, cultural, and interactional roles. The socialization of values and the formation of students’ multicultural identities are achieved through the integration of multicultural values into Civic Education (PPKn) lessons and extracurricular activities such as Scouting, Red Cross (PMR), Student Council (OSIS), the Flag Raising Brigade (Paskibra), and dance. The effectiveness of the school’s role in building social cohesion amidst diversity is influenced by supporting factors such as principal support, teacher training and development, and adequate facilities and infrastructure, while inhibiting factors include the continued existence of a small number of students with exclusive attitudes and the inadequacy of multicultural socialization outside the school environment.